Transformational Leadership and Workload Driving Performance through Innovation and Job Satisfaction in Rural Education - Partiwi, Marsa Hijro; Hendra, Robi; Muazza, Muazza; Yanto, Yanto (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
This study examines how transformational leadership and workload drive teacher performance through innovative work behaviour and job satisfaction in a rural educational context. While previous studies have explored these variables separately, empirical evidence integrating leadership, workload, innovation, and satisfaction within rural education settings remains limited. Using a quantitative cross-sectional design, data were collected from 362 teachers in Kerinci District, Jambi Province, Indonesia, and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that transformational leadership significantly influences innovative work behaviour (β = 0.386, p < 0.001) and job satisfaction (β = 0.120, p = 0.010). Workload emerges as the strongest predictor of innovative work behaviour (β = 0.578, p < 0.001) and job satisfaction (β = 0.648, p < 0.001). Furthermore, innovative work behaviour (β = 0.171, p = 0.015) and job satisfaction (β = 0.497, p < 0.001) positively affect teacher performance. These findings highlight that teacher performance in rural education is shaped not only by inspirational leadership but also by structured and manageable workloads that foster innovation and satisfaction. This study contributes to leadership and organizational behaviour literature by clarifying the mechanisms through which leadership and workload influence performance in developing-region educational contexts and offers practical implications for school leadership and educational policy.